The Effectiveness Of Face To Face And Internet-Based Mindfulness-Based Cognitive Therapy Group Counseling To Enhance Subjective Well-Being - Fuadina, Nabila; Sutoyo, Anwar; Murtadho, Ali (Universitas Negeri Semarang, 2023)
Subjective well-being supports the learning quality which later helps students increase their potential. Therefore, the present study aimed at examining the effectiveness of face to face and internet-based mindfulness-based cognitive therapy group counseling to enhance subjective well-being. It used a randomized pretest posttest comparison group design with two experimental groups and involved 12 students selected using the purposive sampling technique from 155 total population of the grade twelve at SMA Negeri 8 Semarang whose subjective well-being were low. Of the analysis, it was found that both face to face and internet-based mindfulness-based cognitive therapy group counseling was effective to enhance the subjective well-being of students at SMA Negeri 8 Semarang.